Determination of local plasma densities with the MARSIS radar: Asymmetries in the high‒altitude Martian ionosphere. Issue 10 (7th October 2013) - Andrews, D. J.; Opgenoorth, H. J.; Edberg, N. J. T.; André, M.; Fränz, M.; Dubinin, E.; Duru, F.; Morgan, D.; Witasse, O.
<x xml:space="preserve">Abstract</x> [1] We present a novel method for the automatic retrieval of local plasma density measurements from the Mars advanced radar for subsurface and ionospheric sounding (MARSIS) active ionospheric sounder (AIS) instrument. The resulting large data set is then used to study the configuration of the Martian ionosphere at altitudes above ∼300 km. An empirical calibration routine is used, which relates the local plasma density to the measured intensity of multiple harmonics of the local plasma frequency oscillation, excited in the plasma surrounding the antenna in response to the transmission of ionospheric sounding pulses. Enhanced accuracy is achieved in higher‒density (ne>150 cm−3) plasmas, when MARSIS AIS is able to directly measure the fundamental frequency of the local plasma oscillation. To demonstrate the usefulness of this data set, the derived plasma densities are binned by altitude and solar zenith angle in regions over weak (|Bc|<20 nT) and strong (|Bc|>20 nT) crustal magnetic fields, and we find clear and consistent evidence for a significant asymmetry between these two regions. We show that within the ∼300–1200 km altitude range sampled, the median plasma density is substantially higher on the dayside in regions of relatively stronger crustal fields than under equivalent illuminations in regions of relatively weaker crustal fields. Conversely, on the nightside, median plasma densities are found to be higher in regions of relatively weaker crustal fields. We suggest that the observed asymmetry arises as a result of the modulation of the efficiency of plasma transport processes by the irregular crustal fields and the generally horizontal draped interplanetary magnetic field.